EFFECT OF PH2S INFLUENCE ON AUSTENITIC STAINLESS STEEL 316L CORROSION BEHAVIOURS IN CHLORIDE ENVIRONMENT / KESAN PENGARUH TEKANAN SEPARA GAS H2S TERHADAP TINGKAH LAKU KAKISAN KELULI TAHAN KARAT 316L DI PERSEKITARAN KLORIDA (Malaysian Journal of Civil Engineering, 2021)
H2S corrosion of equipment and pipeline system failures in oil and gas industry is a major concern of researchers as it involves high maintenance costs. Therefore, this study discusses the effect of H2S partial pressure at 0, 3 and 15 bar towards the corrosion behaviour of 316L austenitic stainless steel in chloride environments. The 316L steel exposed to 0 bar pH2S was slightly corroded due to the presence of Cr element which has increased the corrosion resistance of the 316L steel. However, pit penetration rate of 316L steel was increased by 90.1% from 0.07 mm/year at 0 bar pH2S to 0.74 mm/year at 3 bar pH2S and decreased by 83.2% at 15 bar pH2S due to the saturated sulfide content in the test solution. Therefore, 316L steel at 3 bar shows highest corrosion effect due to the dissolution of Cr element at 316L steels surface, thus enhanced passive film breakdown.